Predikativy tekstovo-obraznì unìversalìì v ukraìnsʹkihnarodnih dumah - Becenko, Tetâna (Stylistyka, 2021)
Article is devoted the analysis of language of the Ukrainian national thoughts. In particu- lar, are considered their basie of text units - tekstovo-shaped universals. The attention is concentrated to the characteristic of predicative tekstovo-shaped structures that corre- spond with sentences. The prepotent words activated for construction of predicative tek- stovo-shaped constructions are analyzed. Predicativc units are described from the point of view of their structural and stylistic singularities.